Innovations and transversalities in the federal executive’s development policies - a historical-documentary approach based on the concept of competencies - O’hara Alves Sobrinho, Francisca Scarlet; Oliveira Barbosa, Lucyana; Siqueira Silva, Maria; de Almeida Bizarria, Fabiana Pinto; Sampaio, Flávia Lorenne Barbosa (Cuadernos de Gobierno y Administración Pública, 2023)
The National Personnel Development Policy (PNDP) aims to train and develop the skills of federal public servants to improve the quality of public management in institutions and offer a service of greater excellence to society. Therefore, this research aims to understand the historical and documentary trajectory of the federal executive’s personnel development policies based on the concept of competencies. To this end, the method used is classified as descriptive, documentary and with a qualitative approach, presenting a historical-documentary path, understanding the personnel development policies of the federal executive between the years 1986 and 2021, supported by the concept of competencies. As main results, it was noticed that constant training supported by the concept of transversal skills is essential for optimizing staff development. Furthermore, there is a need to build an organizational environment conducive to identifying and promoting internal corporate leadership. In the field of practical application, this study contributes to a better understanding of the trajectory of public servant development policies.